(3CfhGQ Gdjbjf aj aVGFd CejQ GdeDefjfs - (3MSf Hf HOQ GdOjf eMeO Hf CMeO Hf jMji GdYdhj GdRjOj,J (B670 (3g` s
(3ChdgG (B:s
(3Chdg eHJhQ , hChd GdehLhO efg (B: (3hELJeGY Edi CLSGeg , eY eGTaY Pdc ef ENJdGa UhQg hgjFGJg hfehg hfHGJg s
(3BNQgG (B:s
(3adGjLhR GdYbO MjfFP dCHi HcQ , hdG bGFd jbhd HCf GdYbO dCHi HcQ ZjQ LGFR hbO bGd HCf GdEeGeI dYdi Ydjg GdSdGe Je GdChd aGdMeO ddg jJdhg Gdbhd ai NjQ GdefRdI s
(3GdfSNI HgG MhGTs
(3cJHJ GdYfhGfGJ HNW fSNi eLhOs
(3HYVgG HGdShGO s
(3hHYVgG HGdMeQI hYdi MhGTjgG bdjd ef GdJUMjMGJ s
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
Keywords: (3GdMOjK h GdeUWdMs